Surprise, Surprise…The continued value of Natural History in contemporary Biology - John L. Koprowski (Mammalogy Notes)
Observation and natural history studies remain important to advancements in science. The value of technology in biological, ecological, and conservation science is indisputable.  From molecular and biochemical methods to high-resolution micro- and macroimagery to global positioning technologies to high-performance computing and applications of artificial intelligence, the ways that we do science have significantly changed in scope and scale to the benefit of science, society, biodiversity and our wild places.  Natural history approaches, broadly described, remain at the heart of scientific endeavor, where we must initiate our investigations with observations using new technologies and pursue them through new analytical approaches by the application of new tools. I write not only to remind us of the importance of such approaches but also to advocate for the continued teaching of skills in observation, exploration and discovery that yield novel insights and perspectives.